An enzyme-free microneedle glucose sensor based on a nickel disulfide film and a preparation method and application thereof
Patent Information
- Application Number
- CN202610837617.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-11
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]解决的技术问题:为解决现有酶基葡萄糖传感器因生物酶易失活和氧依赖导致的长期稳定性不足,以及现有无酶微针传感器敏感层附着力弱、灵敏度低、难以兼顾机械强度与电催化性能的技术难题,本发明提供一种基于四硫化镍二钴薄膜的无酶微针葡萄糖传感器及其制备方法和应用,能够在微针表面原位构建具有微纳米多孔结构的高附着力敏感层,通过镍钴协同催化效应显著提升葡萄糖氧化电流响应,实现组织间质液中微摩尔级葡萄糖浓度的稳定、灵敏和微创检测
[0017]有益效果:本发明通过多步重复电化学沉积工艺,在导电微针表面原位生长四硫化镍二钴复合薄膜,以此构建无酶葡萄糖敏感层。在薄膜附着力方面,采用沉积-冲洗-干燥的多步循环制备方式,使每次沉积的薄膜在前一层基础上继续外延生长,单次沉积中可能存在的微区缺陷被后续沉积所填充和修补,最终形成连续致密的膜层。扫描电子显微镜观察显示,经三次重复沉积后薄膜完整覆盖针尖区域,未见裂纹或裸露基底。模拟皮肤穿刺实验中,微针刺入琼脂凝胶后针体无弯曲,敏感层未发生剥落,表明该薄膜具备承受透皮力学载荷的机械可靠性。在电催化活性方面,四硫化镍二钴薄膜中镍和钴双金属硫化物产生了显著的协同催化效应。通过系统优化前驱体溶液中镍钴摩尔比和硫源浓度,确定镍钴比为1:2、硫代硫酸钠浓度为0.1M时,薄膜中高价态镍离子和钴离子的电对催化效率达到最佳匹配,葡萄糖氧化峰电流较其他配比配方提升达两倍以上。高倍电子显微镜图像进一步揭示,该工艺条件下制备的敏感膜层呈现微纳米级多孔颗粒状堆积形貌,比表面积明显增加,为葡萄糖分子提供了丰富的吸附位点和反应界面。在检测性能方面,基于上述结构协同和组分协同的优势,传感器对葡萄糖浓度变化表现出灵敏且稳定的电化学响应。实验测得传感器的线性检测范围为929-3476μM,灵敏度为5.65μV·μM-1·cm-2,检测限低至3.99μM,可覆盖组织间质液中葡萄糖浓度的正常与异常波动区间。同一传感器十次重复测试的相对标准偏差仅为2.22%,体现出良好的短期检测重现性。在微创无痛透皮监测方面,微针有效长度控制在500μm至1000μm范围内,恰好穿透皮肤角质层抵达富含组织间质液的表皮层,而未触及真皮层痛觉神经末梢和毛细血管。配合薄膜本身优异的机械附着性能,传感器可在无痛条件下实现皮下葡萄糖的原位连续监测,为糖尿病患者的长期血糖管理提供了可靠的微创检测手段。
Smart Images

Figure CN122879783A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biosensor technology, specifically relating to an electrochemical glucose sensor, and more particularly to an enzyme-free microneedle glucose sensor based on a nickel dicobalt tetrasulfide thin film, its preparation method, and its application. Background Technology
[0002] Diabetes mellitus is a metabolic disease characterized by chronic hyperglycemia, affecting over 500 million people worldwide and continuing to grow. Poor long-term blood glucose control can lead to serious complications such as retinopathy, kidney failure, nerve damage, and cardiovascular disease. Intermittent or persistent hyperglycemia can cause irreversible damage to multiple organ systems. Against this medical backdrop, frequent, continuous, and accurate blood glucose monitoring is of paramount clinical value for the daily management of diabetic patients, adjustment of treatment plans, and prevention of complications. However, traditional finger-prick blood sampling methods, due to their high pain levels, limited sampling frequency, and difficulty in nighttime monitoring, are no longer sufficient to meet the needs of precision medicine for continuous dynamic blood glucose data acquisition. Microneedle sensors, which can be minimally invasively inserted into the stratum corneum to reach the epidermis and obtain interstitial fluid without touching capillaries and dermal pain nerves, have become an important development direction in continuous blood glucose monitoring technology in recent years.
[0003] Currently, most mature electrochemical glucose sensors in clinical and research fields are based on the detection principle of glucose oxidase-modified working electrodes. These enzyme-based sensors exhibit good substrate selectivity, but the inherent molecular fragility of biological enzymes leads to insufficient long-term stability. Slight fluctuations in temperature, humidity, and pH can cause enzyme activity decay or even complete inactivation, imposing stringent requirements on storage conditions and operating environments. More importantly, the enzymatic glucose oxidation reaction is highly dependent on dissolved oxygen as a natural electron acceptor. When microneedles are inserted into the skin, the oxygen partial pressure in the interstitial fluid is much lower than in the atmospheric environment. Insufficient oxygen supply limits the rate of enzyme-catalyzed reactions, causing the sensor's signal response under real physiological conditions to deviate from the in vitro pre-calibrated values. This oxygen-limiting effect is often particularly pronounced in hypoxic tissues and is difficult to completely resolve with simple signal compensation algorithms.
[0004] To circumvent the inherent drawbacks of enzyme inactivation and oxygen dependence, significant progress has been made in enzyme-free glucose sensors based on inorganic sensitive materials such as metals and their oxides, and sulfides. These sensors directly electrocatalyze the oxidation of glucose molecules without the need for biological enzymes, thus eliminating the problems of enzyme stability and oxygen flux limitations at the fundamental level. However, when these inorganic sensitive materials are modified onto the surface of microneedle substrates through coating or deposition, the film adhesion performance is often unsatisfactory. Under the mechanical stress of microneedles penetrating the skin, cracking and peeling easily occur, leading to in vivo sensor failure. Furthermore, existing preparation methods have limited means to finely control the microstructure of the sensitive layer, making it difficult to construct an electrocatalytic interface with high specific surface area and multiple active sites on the limited outer surface area of the microneedles. This prevents the intrinsic catalytic performance of the sensitive material from being fully released, and the sensor sensitivity and detection limit are often insufficient to meet the requirements for accurate detection of micromolar concentrations of glucose in interstitial fluid.
[0005] In summary, achieving the long-term stability lacking in enzyme-based sensors, overcoming the dual shortcomings of weak adhesion and insufficient sensitivity of enzyme-free sensors on microneedle surfaces, and constructing a minimally invasive glucose sensor that can combine mechanical reliability and electrochemical response performance in complex physiological environments are key issues that urgently need to be addressed in the field of continuous blood glucose monitoring technology. Summary of the Invention
[0006] Technical problems solved: To address the insufficient long-term stability of existing enzyme-based glucose sensors due to the easy inactivation of biological enzymes and oxygen dependence, as well as the technical difficulties of existing enzyme-free microneedle sensors such as weak adhesion of the sensitive layer, low sensitivity, and difficulty in balancing mechanical strength and electrocatalytic performance, this invention provides an enzyme-free microneedle glucose sensor based on nickel dicobalt tetrasulfide thin film, its preparation method, and its application. It can construct a highly adhesive sensitive layer with a micro-nano porous structure in situ on the microneedle surface, and significantly improve the glucose oxidation current response through the nickel-cobalt synergistic catalytic effect, realizing stable, sensitive, and minimally invasive detection of micromolar glucose concentration in interstitial fluid.
[0007] Technical Solution: A method for preparing an enzyme-free microneedle glucose sensor based on a nickel dicobalt tetrasulfide thin film, comprising the following steps: using a conductive microneedle as the cathode, immersing it in an electroplating solution containing a soluble nickel salt, a soluble cobalt salt, and a soluble sulfur source; applying a DC voltage for electrochemical deposition; after deposition, removing the microneedle for rinsing and drying; repeating the electrochemical deposition and rinsing-drying steps 2 to 4 times to form a nickel dicobalt tetrasulfide composite film with a micro / nano porous structure on the surface of the conductive microneedle; the soluble nickel salt is nickel acetate with a concentration of 0.005 mol / L to 0.02 mol / L; the soluble cobalt salt is cobalt acetate with a concentration of 0.01 mol / L to 0.03 mol / L; the soluble sulfur source is sodium thiosulfate with a concentration of 0.05 mol / L to 0.2 mol / L; the DC voltage is 3V to 7V; and the time for a single electrochemical deposition is 40 seconds to 80 seconds.
[0008] Preferably, the concentration of nickel acetate is 0.01 mol / L, the concentration of cobalt acetate is 0.02 mol / L, and the concentration of sodium thiosulfate is 0.1 mol / L.
[0009] Preferably, the DC voltage is 5V, the time for a single electrochemical deposition is 60 seconds, and the electrochemical deposition and rinsing-drying steps are repeated 3 times.
[0010] The conductive microneedle substrate described above also includes polishing and acid immersion activation treatment before electrochemical deposition, and the electrochemical deposition area is limited to the tip of the conductive microneedle.
[0011] An enzyme-free microneedle glucose sensor based on a nickel dicobalt tetrasulfide thin film was prepared by the above method.
[0012] In the above-mentioned nickel tetrasulfide cobalt-1 composite film, the molar ratio of nickel to cobalt is 1:2.
[0013] The effective transdermal length of the aforementioned conductive microneedle substrate is 500 μm to 1000 μm.
[0014] The aforementioned enzyme-free microneedle glucose sensor also includes a reference electrode and an auxiliary electrode. The conductive microneedle substrate serves as the working electrode and is assembled together with the reference electrode and the auxiliary electrode on an insulating substrate to form a three-electrode system.
[0015] The above-mentioned enzyme-free microneedle glucose sensor is used to detect glucose concentration in biological fluids, wherein the biological fluids are interstitial fluid, sweat, blood, urine, or tears.
[0016] The aforementioned biological fluid is interstitial fluid.
[0017] Beneficial Effects: This invention utilizes a multi-step, repetitive electrochemical deposition process to grow a nickel-cobalt tetrasulfide composite film in situ on the surface of conductive microneedles, thereby constructing an enzyme-free glucose-sensitive layer. Regarding film adhesion, a multi-step cyclical preparation method of deposition-rinsing-drying is employed, allowing each deposited film to continue epitaxial growth on top of the previous layer. Micro-defects that may exist in a single deposition are filled and repaired by subsequent depositions, ultimately forming a continuous and dense film layer. Scanning electron microscopy observation shows that after three repeated depositions, the film completely covers the needle tip area, with no cracks or exposed substrate observed. In simulated skin puncture experiments, the microneedle did not bend after piercing the agar gel, and the sensitive layer did not peel off, indicating that the film possesses the mechanical reliability to withstand transdermal mechanical loads. Regarding electrocatalytic activity, the nickel and cobalt bimetallic sulfides in the nickel-cobalt tetrasulfide film exhibit a significant synergistic catalytic effect. By systematically optimizing the nickel-cobalt molar ratio and sulfur source concentration in the precursor solution, it was determined that a nickel-cobalt ratio of 1:2 and a sodium thiosulfate concentration of 0.1 M resulted in the optimal match of the redox efficiency between high-valence nickel and cobalt ions in the film, with the glucose oxidation peak current being more than twice that of other formulations. High-magnification electron microscopy images further revealed that the sensitive film prepared under these conditions exhibited a micro / nano-scale porous particle-like morphology, with a significantly increased specific surface area, providing abundant adsorption sites and reaction interfaces for glucose molecules. Regarding detection performance, based on the aforementioned structural and component synergies, the sensor demonstrated a sensitive and stable electrochemical response to changes in glucose concentration. Experimentally, the sensor's linear detection range was measured to be 929–3476 μM, and its sensitivity was 5.65 μV·μM. -1 ·cm -2 With a detection limit as low as 3.99 μM, it can cover the normal and abnormal fluctuation range of glucose concentration in interstitial fluid. The relative standard deviation of ten repeated tests with the same sensor is only 2.22%, demonstrating good short-term detection reproducibility. In terms of minimally invasive and painless transdermal monitoring, the effective length of the microneedle is controlled within the range of 500 μm to 1000 μm, which precisely penetrates the stratum corneum to reach the epidermal layer rich in interstitial fluid, without touching the pain nerve endings and capillaries in the dermis. Combined with the excellent mechanical adhesion properties of the membrane itself, the sensor can achieve in-situ continuous monitoring of subcutaneous glucose under painless conditions, providing a reliable minimally invasive detection method for long-term blood glucose management in diabetic patients. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the fabrication and assembly process of the microneedle sensor of the present invention. The present invention uses an electrochemical deposition method to form a NiCo2S4 composite film on the surface of the microneedles through multiple repeated deposition steps in an electroplating solution containing nickel salt, cobalt salt and sulfur source, using conductive microneedles as a substrate, and finally assembling them into a three-electrode sensor.
[0019] Figure 2This is a photograph of the assembled microneedle array.
[0020] Figure 3 These are scanning electron microscope (SEM) images of the microneedle working electrode surface at different magnifications. Low-magnification SEM: The film completely covers the needle tip without obvious cracks or peeling, indicating good macroscopic mechanical stability. High-magnification SEM: The film surface exhibits a micro / nano-scale porous granular structure. This structure greatly increases the specific surface area of the electrode, providing abundant adsorption sites and catalytic reaction interfaces for glucose molecules.
[0021] Figure 4 These are comparative images of the surface morphology of microneedles after single electrochemical deposition and triple electrochemical deposition. In image a, the conductive microneedle substrate is shown as a macroscopic object with a size scale; in image b, the microneedles appear after different deposition cycles. The upper microneedle represents triple electrochemical deposition, and the lower microneedle represents single electrochemical deposition. Single deposition (60 seconds): The film is thin, light in color, unevenly distributed, and has exposed areas of the metal substrate. Triple deposition: The surface is completely encapsulated by a deep black NiCo2S4 layer; the film is thick and uniform.
[0022] Figure 5 The graph shows the effect of different precursor concentration ratios in electroplating solutions on the cyclic voltammetric response. In the graph, a represents the cyclic voltammetric curves under different nickel-cobalt molar ratios, and b represents the cyclic voltammetric curves under different sodium thiosulfate concentrations.
[0023] Figure 6 The image shows the cyclic voltammetric response of the sensor in sodium hydroxide solutions containing different concentrations of glucose. In the image, a represents the CV image of a single cycle scan, b represents the CV images of glucose solutions at different concentrations, c represents the CV images of glucose solutions at different concentrations within the effective range, and d represents the linear fit between concentration and peak difference.
[0024] Figure 7 This is a linear response fitting graph of the sensor to glucose concentration. In the graph, a is the original test curve, b is the open-circuit voltage curve within the effective range, c is the average value of the stable segment of the open-circuit voltage curve at different concentrations, and d is the linear fit between concentration and open-circuit voltage.
[0025] Figure 8 Microscopic images of the transdermal depth test after a microneedle array is inserted into simulated skin agar gel.
[0026] Figure 9 The results show the long-term stability of the microneedle glucose sensor under continuous cyclic voltammetry testing; a is the representative cyclic voltammetry curve at different number of cycles, and b is the curve showing the change in the oxidation response current retention rate during 100 consecutive forward scans. Detailed Implementation
[0027] Those skilled in the art should understand that various equivalent substitutions or modifications can be made to the above specific embodiments without departing from the spirit and essence of the present invention, and all such substitutions or modifications fall within the protection scope of the present invention.
[0028] Example 1
[0029] 1. Substrate pretreatment: Take a medical stainless steel microneedle (approximately 1.5 mm in length, with a tip curvature radius of <10 μm), and polish the tip with 400, 800, and 1200 grit sandpaper in sequence. Then, immerse it in 0.1 M HCl for ultrasonic cleaning for 5 minutes, rinse with deionized water, and dry with nitrogen.
[0030] 2. Preparation of electroplating solution: Weigh 0.249g nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O, 0.01mol), 0.498g cobalt acetate tetrahydrate (Co(CH3COO)2·4H2O, 0.02mol), and 2.482g sodium thiosulfate pentahydrate (Na2S2O3·5H2O, 0.1mol), dissolve them in deionized water, and bring the volume to 1L. Stir for 30 minutes until completely dissolved.
[0031] 3. Electrochemical deposition: Using microneedles as the cathode and platinum sheet electrodes as the anode, the electrodes are immersed in the electroplating solution. A DC voltage of 5V is applied, and deposition takes 60 seconds.
[0032] 4. Rinsing and drying: Remove the microneedles, rinse them three times with deionized water, and dry them in a 40°C oven for 10 minutes.
[0033] 5. Repeated deposition: Repeat steps 3 and 4 a total of 3 times. The final microneedle surface exhibits a uniform, deep black NiCo2S4 film.
[0034] 6. Sensor Assembly: Three prepared microneedles were fixed on a polyimide insulating substrate at a spacing of 500 μm, and copper wires were led out from each. An Ag / AgCl reference electrode and a platinum wire auxiliary electrode were simultaneously integrated on the substrate. The area except for the microneedle tips was encapsulated with epoxy resin to obtain a three-electrode microneedle sensor for detection in subsequent embodiments.
[0035] Example 2
[0036] Electroplating solution formulation optimization experiment
[0037] 1. Effect of different Ni:Co molar ratios on electrochemical response
[0038] Methods: Microneedle electrodes prepared with a fixed sodium thiosulfate concentration of 0.1 mol / L were tested at Ni:Co molar ratios of 1:5, 1:2, 1:1, and 2:1. CV scans were performed in a 0.1 M NaOH solution containing 3.0 mM glucose.
[0039] result( Figure 5 a) When Ni:Co = 1:2, the glucose oxidation peak current reaches its maximum value, significantly higher than other ratios, and the integral area of the CV curve is the largest. This indicates that the 1:2 ratio can maximize the synergistic electrocatalytic effect of Ni and Co.
[0040] 2. Effect of different sodium thiosulfate concentrations on electrochemical response
[0041] Method: With the Ni:Co ratio fixed at 1:2, the concentrations of sodium thiosulfate were tested at 0.05, 0.1, and 0.2 mol / L.
[0042] result( Figure 5 b): The peak current is optimal at 0.1 mol / L. Too low a concentration (0.05 mol / L) results in incomplete metal sulfidation and a very small catalytic current; too high a concentration (0.2 mol / L) does produce a response, but the peak shape and current value are slightly inferior to those at 0.1 mol / L, which is speculated to cause surface particle agglomeration.
[0043] Conclusion: The preferred electroplating solution ratio (0.01M nickel acetate, 0.02M cobalt acetate, and 0.1M sodium thiosulfate) of this invention represents the optimal process conditions.
[0044] Example 3
[0045] Electrochemical performance testing
[0046] 1. Cyclic Voltammetry (CV) Test
[0047] Test conditions: CV scans were performed at a scan rate of 50 mV / s in 0.1 M NaOH solutions containing different concentrations of glucose (1.0~5.0 mM).
[0048] result( Figure 6 As the glucose concentration increases, the oxidation peak current near the 0.45V potential increases significantly, indicating that the NiCo2S4 film has a significant electrocatalytic oxidation effect on glucose.
[0049] Example 4
[0050] Sensitivity and Linear Range
[0051] Test method: The steady-state current response at different glucose concentrations was recorded using the chronoamperometry (or open-circuit potential method).
[0052] result( Figure 7 ):
[0053] Linear detection range: 929μM ~ 3476μM
[0054] Linear fitting equation: I (μA) = 0.0565·C (μM) + 0.23, R2 = 0.986
[0055] Sensitivity: 5.65 μV·μM -1 ·cm -2 (Or converted to current sensitivity)
[0056] Limit of detection (LOD): 3.99 μM (S / N=3)
[0057] Stability and reproducibility
[0058] Method: Ten repeated tests were performed on the same sensor (with the same glucose concentration), and the relative standard deviation (RSD) of the response current was calculated.
[0059] Results: RSD = 2.22%, indicating that the sensor has excellent reproducibility and short-term stability.
[0060] Example 5
[0061] Mechanical properties and transdermal testing
[0062] 1. Simulated skin puncture experiment
[0063] Methods: In vitro puncture tests were conducted using an agar gel model (3% agar, which has mechanical properties similar to human skin). A microneedle array was vertically pressed into the gel block, and the needle's condition was observed under a microscope, with the insertion depth measured.
[0064] result( Figure 8 ):
[0065] The microneedle array easily penetrates the agar surface without bending, breaking, or shedding of the sensitive membrane.
[0066] The actual effective transdermal depth is approximately 800 μm, falling within the preferred range of 500–1000 μm.
[0067] Conclusion: The microneedle sensor of the present invention meets the requirements of "minimally invasive and painless" continuous monitoring in terms of physical structure, and the sensitive layer has sufficient mechanical adhesion.
[0068] Comparison of effects data
[0069] To more intuitively demonstrate the improvement of electrocatalytic performance by the optimized process, peak values were extracted from the CV curves under different ratio conditions. Each data file contains 5 scan lines. Table 1 shows the peak current of the second forward scan line within the glucose oxidation peak range, with the current unit converted from A to mA.
[0070] Table 1
[0071]
[0072] As shown in the table, when the sodium thiosulfate concentration is fixed at 0.10 mol / L, the oxidation peak current of the Ni:Co=1:2 group is 1.716 mA, which is higher than that of the 1:5, 1:1 and 2:1 ratios. When the Ni:Co is fixed at 1:2, the 0.10 mol / L sodium thiosulfate group is also higher than the low sulfur group and slightly higher than the high sulfur group, indicating that the nickel-cobalt synergistic catalysis and the degree of sulfidation are well matched under this formulation.
[0073] Example 6 Long-term stability test
[0074] To verify the stability of the microneedle glucose sensor of this invention during continuous electrochemical testing, the microneedle sensor prepared in Example 1 was placed in an alkaline test solution containing 0.3 mmol / L glucose for continuous cyclic voltammetry scanning. The test potential range was 0-0.9 V, and 200 scan segments were performed continuously, including 100 forward scan responses. Because one set of test data was affected by external interference and the experiment was stopped midway, it was not included in the stability evaluation; only the two sets of complete sample data were selected for analysis.
[0075] The glucose oxidation response current at approximately 0.845 V during the forward scan was used as the evaluation index, and the response currents for the 1st, 10th, 20th, 40th, 60th, 80th, and 100th forward scans were extracted. The results (Table 2) show that the oxidation response current of sample 1 was 3.306 mA at the 10th forward scan and 3.144 mA at the 100th forward scan, with a current retention rate of 95.1%; the oxidation response current of sample 2 was 3.936 mA at the 10th forward scan and 3.824 mA at the 100th forward scan, with a current retention rate of 97.2%. These results indicate that after 100 consecutive forward cyclic voltammetric scans, the glucose oxidation response current of the sensor only slightly decreased, maintaining more than 95% of the initial stable response, demonstrating that the NiCo2S4 sensing layer has good long-term electrochemical stability and reusability.
[0076] Table 2
[0077]
[0078] This invention is not limited to the above embodiments and can be modified and extended in various ways: In addition to stainless steel, the substrate material can be metal microneedles such as gold, platinum, or titanium, or polymer microneedles coated with conductive polymers (such as PEDOT:PSS); the nickel salt can be nickel chloride, nickel sulfate, or nickel nitrate; the cobalt salt can be cobalt chloride, cobalt sulfate, or cobalt nitrate; the sulfur source can be thiourea, sodium sulfide, or thioacetamide; the electroplating parameters can be adjusted to a voltage of 3~7V. The deposition time is adjustable within the range of 40-80 seconds per deposition and 2-4 repetitions, and can be appropriately adjusted according to the microneedle size and electroplating solution concentration to still form an effective NiCo2S4 thin film. The deposition method can use a three-electrode system (working, reference, and auxiliary) for constant potential deposition, or pulse electroplating can be used instead of DC electroplating. When assembling the electrodes, the reference electrode can be a saturated calomel electrode (SCE) or a pseudo-reference electrode (such as a platinum wire), and the auxiliary electrode can be gold, carbon, or graphite. In addition to interstitial fluid and sweat, it can also be used to detect glucose in blood, urine, and tears. In addition to equidistant arrays, the microneedle array can also be arranged in a ring, staggered, or other irregular configurations.
Claims
1. A method for preparing an enzyme-free microneedle glucose sensor based on a nickel dicobalt tetrasulfide thin film, characterized in that, Includes the following steps: Using conductive microneedles as cathodes, they are immersed in an electroplating solution containing soluble nickel salts, soluble cobalt salts, and a soluble sulfur source. A DC voltage is applied for electrochemical deposition. After deposition, the microneedles are removed, rinsed, and dried. This electrochemical deposition and rinsing-drying process is repeated 2 to 4 times to form a nickel-cobalt tetrasulfide composite film with a micro / nano porous structure on the surface of the conductive microneedles. The soluble nickel salt is nickel acetate with a concentration of 0.005 mol / L to 0.02 mol / L; the soluble cobalt salt is cobalt acetate with a concentration of 0.01 mol / L to 0.03 mol / L; the soluble sulfur source is sodium thiosulfate with a concentration of 0.05 mol / L to 0.2 mol / L; the DC voltage is 3V to 7V; and the time for a single electrochemical deposition is 40 to 80 seconds.
2. The preparation method according to claim 1, characterized in that, The concentration of nickel acetate is 0.01 mol / L, the concentration of cobalt acetate is 0.02 mol / L, and the concentration of sodium thiosulfate is 0.1 mol / L.
3. The preparation method according to claim 2, characterized in that, The DC voltage is 5V, the time for a single electrochemical deposition is 60 seconds, and the electrochemical deposition and rinsing-drying steps are repeated 3 times.
4. The preparation method according to claim 1, characterized in that, The conductive microneedle substrate also includes polishing and acid immersion activation treatment before electrochemical deposition, and the electrochemical deposition area is limited to the tip of the conductive microneedle.
5. An enzyme-free microneedle glucose sensor based on a nickel dicobalt tetrasulfide thin film, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 4.
6. The enzyme-free microneedle glucose sensor according to claim 5, characterized in that, The molar ratio of nickel to cobalt in the nickel tetrasulfide cobalt-1 composite film is 1:
2.
7. The enzyme-free microneedle glucose sensor according to claim 5, characterized in that, The effective transdermal length of the conductive microneedle substrate is 500 μm to 1000 μm.
8. The enzyme-free microneedle glucose sensor according to claim 5, characterized in that, It also includes a reference electrode and an auxiliary electrode. The conductive microneedle substrate serves as the working electrode and is assembled together with the reference electrode and the auxiliary electrode on an insulating substrate to form a three-electrode system.
9. The application of the enzyme-free microneedle glucose sensor of claim 5 in detecting glucose concentration in biological fluids, wherein the biological fluid is interstitial fluid, sweat, blood, urine, or tears.
10. The application according to claim 9, characterized in that, The biological fluid in question is interstitial fluid.